KELUARGA KRISTIANI SEBAGAI LAHAN BERTUMBUHNYA BENIH-BENIH PANGGILAN PEWARTA KRISTIANI - Albert I Ketut Deni Wijaya; Maria Natalia (Lembaga Penelitian STKIP Widya Yuwana, 2019)
In this very modern age, families run into changes. Changes in lifestyle, way to educate, knowledge, and soon. These changes have an impact on Christian evangelizers vocation. Even today, it is rarely that the parents let their children to become an evangelizer. The thing such like this is very unfortunate because the evangelizer is very less power whereas the Church still needs them. Nevertheless there are still also christian families who remained faithful in preserving christian values. Parents have an important role to instill christian values to their children in order to support the success of the instilling evangelizer vocations.